PENGEMBANGAN E-MODUL BIMBINGAN KARIER UNTUK MENINGKATKAN KEMAMPUAN PESERTA DIDIK DALAM MEMILIH MATA PELAJARAN PADA KURIKULUM MERDEKA - Gali, Andi Haerul; Buchori, Sahril; Pandang, Abdullah (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2024)
This study aims to develop and test the effectiveness of a Career Guidance E-Module in assisting students in selecting subjects under the Merdeka Curriculum. The E-Module is designed to provide interactive guidance on exploring interests, talents, and career planning independently. The method used is Research and Development (R&D) with the Borg and Gall model, involving validation stages and practicality testing. The research was conducted at UPT SMAN 1 Pangkep, involving 30 students for the needs analysis. Product validation was carried out by 2 experts, namely a career guidance expert and a media expert, to assess the quality of the content and the design of the E-Module. The practicality test was conducted with 5 students and 1 career guidance teacher. The results showed that the E-Module is valid, with scores of 85% from content experts and 88% from media experts, and practical, with scores of 82% from students and 84% from the career guidance teacher. The E-Module is able to enhance students' understanding in selecting subjects according to their interests and career goals, supporting the flexibility of learning provided by the Merdeka Curriculum